Impact of coronavirus 2019 on mental health and lifestyle adaptations of pregnant women in the United Arab Emirates: a cross-sectional study - Mona Hashim; Ayla Coussa; Ayesha S. Al Dhaheri; Amina Al Marzouqi; Samer Cheaib; Anastasia Salame; Dima O. Abu Jamous; Farah Naja; Hayder Hasan; Lily Stojanovska; Maysm N. Mohamad; Mo’ath F. Bataineh; et al. (BMC Pregnancy and Childbirth, 2021)
Abstract Background In light of the pandemic, pregnant women are particularly vulnerable to increased psychological distress and in need of imperative preventive measures. This study aimed to investigate the impact of the pandemic on mental health, lifestyle adaptations, and their determinants among pregnant women in the United Arab Emirates. Methods A survey was conducted electronically between June and August 2020. Pregnant women were recruited from prenatal clinics in the UAE and invited to participate in an online survey developed on Google Forms. The questionnaire included socio-demographic characteristics, the Impact of Event Scale- Revised, the Perceived Support Scale and lifestyle-related factors. Results A total of 384 pregnant women completed the questionnaire of whom 20.6% were in their 1st trimester, 46.1% in their 2nd and 33.3% in their 3rd trimester. The mean IES-R score for the respondents was 26.15 ± 13.55, corresponding to a mild stressful impact, which did not differ significantly among trimesters of pregnancy. Pregnant women expressed increased stress from staying home (64%), work (40%), feeling frightened (66%) and apprehensive (59%). Women reported increased support and sharing their feelings with family members (59%), mainly in the 1st and 3rd trimester of pregnancy (P < 0.05). There was a greater attention to mental health (48%), resting time (55.3%), and relaxing time (57.3%); while a decreased amount of time was spent engaging in physical activities (53.6%), which differed significantly between trimesters (P = 0.02). Conclusions The COVID-19 pandemic was associated with a mild stressful impact among pregnant women in the UAE, braced by strong family support and self-care mental health behaviors.